2021
DOI: 10.1002/app.51872
|View full text |Cite
|
Sign up to set email alerts
|

A multilayer transparent wood prepared by laminating two kinds of tree species

Abstract: Transparent wood (TW) is a new material with a certain light transmission performance, which can be widely used as new energy-saving material. However, the application and development of TW are limited by material and thickness. In this work, the representative species of softwood and hardwood were selected for lamination. After chemical treatment, the lignin in natural wood was removed, and then the epoxy resin with a similar refractive index to the cell wall was impregnated in vacuum. By using the viscosity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…The wave numbers of the epoxy resin H758 are 2962 cm –1 (symmetric stretching vibration of C–H group on CH 3 ), 2860 cm –1 (antisymmetric stretching vibration of C–H group on CH 3 ), 1606 and 1506 cm –1 (asymmetric vibration band of benzene ring skeleton), 1456 and 734 cm –1 . The characteristic peaks at CH 3 shear oscillation, 1243 cm –1 (stretching vibration of adipose ether C–O–C) and 827 cm –1 (out-of-plane deformation of para-substituted benzene ring CH) are consistent with previous studies …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wave numbers of the epoxy resin H758 are 2962 cm –1 (symmetric stretching vibration of C–H group on CH 3 ), 2860 cm –1 (antisymmetric stretching vibration of C–H group on CH 3 ), 1606 and 1506 cm –1 (asymmetric vibration band of benzene ring skeleton), 1456 and 734 cm –1 . The characteristic peaks at CH 3 shear oscillation, 1243 cm –1 (stretching vibration of adipose ether C–O–C) and 827 cm –1 (out-of-plane deformation of para-substituted benzene ring CH) are consistent with previous studies …”
Section: Resultsmentioning
confidence: 99%
“…The characteristic peaks at CH 3 shear oscillation, 1243 cm –1 (stretching vibration of adipose ether C–O–C) and 827 cm –1 (out-of-plane deformation of para-substituted benzene ring =CH) are consistent with previous studies. 30 …”
Section: Resultsmentioning
confidence: 99%
“…After dyeing treatment of DW, it can be observed that the skeleton vibration of RW increases at 1641 cm −1 , which corresponds to the triazine ring in the dye structure, and the stretching vibration of C−O−C increases at 1160 cm −1 , indicating that the dyed wood contains reactive red X-3B and there may be the formation of dye fiber covalent bonds. 18 Characteristic bands of 2954 cm −1 , 1135 cm −1 (C−H vibration), and 1724 cm −1 (C�O vibration) were found in the infrared spectra of TW and RTW. These bands are related to UV resin, indicating that UV resin successfully impregnated the stained and unstained wood templates.…”
Section: Methodsmentioning
confidence: 95%
“…Under the environmental protection goal of carbon neutrality and carbon peak, sustainable manufacturing has become the new development direction of the manufacturing industry. This has led to a focus on recycling and the conservation of natural resources and energy in furniture manufacturing processes [1][2][3]. Particle boards (PBs) as a kind of wood-based panel, are widely applied for the manufacturing of custom furniture in China [4][5][6] and milling occupies a large proportion of that manufacturing process [7,8].…”
Section: Introductionmentioning
confidence: 99%